Game changer eaudiobook - Greenwald, Tommy (Tantor Media, 2020)
Thirteen-year-old Teddy Youngblood is in a coma fighting for his life after an unspecified football injury at training camp. His family and friends flock to his bedside to support his recovery—and to discuss the events leading up to the tragic accident. Was this an inevitable result of playing a violent sport, or was something more sinister happening on the field that day? Told in an innovative, multimedia format combining dialogue, texts, newspaper articles, transcripts, an online forum, and Teddy's inner thoughts, Game Changer explores the joyous thrills and terrifying risks of America's most popular sport.